The Role of the Respiratory Therapy Team in the Treatment of Patients With Acquired Immunodeficiency Syndrome Complicated With Pneumocystis Pneumonia Undergoing Mechanical Ventilation - Yanmei Gu; Shuangmei Xi; Boxun Jin; Huimin Guo; Jiankun Yang; Xin Liu; Xiulian Wu; Lili Zhang; Guangming Li (Frontiers Media S.A., 2022)
ObjectiveTo explore the role of the respiratory therapy team in the treatment of patients with acquired immunodeficiency syndrome (AIDS) complicated with pneumocystis pneumonia (PCP) undergoing mechanical ventilation.MethodsA retrospective cross-sectional study was conducted, including 60 patients with AIDS complicated with PCP undergoing mechanical ventilation in our hospital from June 2019 to July 2020. In the process of patient respiratory monitoring, hospital transport, ventilator withdrawal, airway management, various aerosol treatments and controlled oxygen therapy, patients were divided into the control group and the case group according to whether the respiratory therapy team was involved or not (30 in the control group, 25 males and five females; 30 in the case group, 24 males and six females). The baseline data, mechanical ventilation time, hospitalization time and hospitalization expenses of the two groups were compared.ResultsThere was no statistically significant difference in baseline data between the case and control groups (P > 0.05). Compared with the control group, the case group had significantly shorter mechanical ventilation times and average hospitalization lengths and the average expenses decreased, and the difference was statistically significant (P < 0.05).ConclusionThe participation of the respiratory therapy team in the mechanical ventilation treatment of patients with AIDS and PCP helps to shorten the mechanical ventilation time and the average length of hospitalization and reduce the hospitalization expenses of patients. It is expected to increase the cure rate of such patients and improve their prognosis.